Analysis of the International Experience in Providing Administrative Services to the Population: What Relevance for its Enforcement in Ukraine? - Zadoia, I. I.; Denysyuk, S.; Tanko, A. V.; Танько, А. В.; Nedrya, K. M. (DIXI. – 2021. – Vol. 23, № 2. – P. 1-14, 2021)
It is a common interest and understanding that providing the population with administrative services is an important aspect for the proper functioning of every given society. There is no society without the proper ma-nagement of its local population. It is to this end that there is a need to examine the position of international law in seeing the administrative management of its population with emphasis in the Ukrainian government. The ob-jective of this article is: 1) to study international experience in providing administrative services; 2) to elaborate propositions for improving the processes related to the provision of administrative services to the population.The experience of foreign countries in the field of providing administrative services to the population (in parti-cular, the United States, Canada and Western Europe) has been analyzed. It has been emphasized that Ukraine needs to build its own system of administrative services, taking into account effective models of carrying out public administration in developed Western countries. It has been noted that the quality of administrative services to the representatives of different segments of the population is one of those criteria, which assists in assessing the effectiveness of the entire state system of the country. It has been emphasized that the service state institution, whose activity is to provide both public and private administrative and legal services, the example of which can be the above-mentioned service institution of the Ministry of Internal Affairs, is only part of the large-scale reform of the existing state legal mechanism in Ukraine that has to change the essence of the functioning of state agencies in this area. The emphasis has been placed on the fact that Ukrainian society, despite some of its own successes, still needs to take many positive steps in the development of the public administration sphere and in the field of providing administrative services to the population.

Доведено, що спільний інтерес і розуміння того, що надання населенню адміністративних послуг є важливим аспектом для нормального функціонування кожного суспільства. Немає суспільства без належного управління місцевим населенням. Саме з цією метою існує необхідність вивчити позицію міжнародного права в баченні адміністративного управління населенням з акцентом на українському уряді. Метою даної статті є: 1) вивчення міжнародного досвіду надання адміністративних послуг; 2) розробити пропозиції щодо вдосконалення процесів, пов’язаних з наданням адміністративних послуг населенню. Досвід зарубіжних країн у сфері надання адміністративних послуг населенню (зокрема, США, Канади та Західної Європи) також було проаналізовано.

Доказано, что общий интерес и понимание того, что предоставление населению административных услуг является важным аспектом для нормального функционирования каждого общества. Нет общества без должного управления местным населением. Именно в этих целях существует необходимость изучить позицию международного права в видении административного управления населением с акцентом на украинском правительстве. Целью данной статьи является: 1) исследование интернационального опыта предоставления административных услуг; 2) разработать предложения по усовершенствованию процессов, связанных с предоставлением административных услуг населению. Опыт зарубежных стран в сфере предоставления административных услуг населению (в частности, США, Канады и Западной Европы) также был проанализирован.

Es de interés común y se entiende que la prestación de servicios administrativos a la población es un aspecto importante para el buen funcionamiento de toda sociedad. No hay sociedad sin una gestión adecuada de su población local. Con este fin, es necesario examinar la posición del derecho internacional al ver la gestión administrativa de su población con énfasis en el gobierno ucraniano. El objetivo de este artículo es: 1) estudiar la experiencia internacional en la prestación de servicios administrativos; 2) elaborar propuestas para mejorar los procesos relacionados con la prestación de servicios administrativos a la población. Se ha analizado la experiencia de países extranjeros en el ámbito de la prestación de servicios administrativos a la población (en particular, Estados Unidos, Canadá y Europa Occidental). Se ha subrayado que Ucrania necesita construir su propio sistema de servicios administrativos, teniendo en cuenta los modelos eficaces para llevar a cabo la administración pública en los países occidentales desarrollados. Se ha observado que la calidad de los servicios administrativos prestados a los representantes de los diferentes segmentos de la población es uno de esos criterios, que ayuda a evaluar la eficacia de todo el sistema estatal del país. esfera de la administración pública y en el ámbito de la prestación de servicios administrativos a la población.
Análisis de la experiencia internacional en la prestación de servicios administrativos a la población: ¿qué relevancia tiene su aplicación en Ucrania?
Análise da experiência internacional na prestação de serviços administrativos à população: Qual a relevância para sua aplicação na Ucrânia?
Keywords: publikatsii u WoS; Ukraine; Україна; administration area; provision of administrative services; public administration; public legal relations; transparent policy; адміністративна сфера; надання адміністративних послуг; державне управління; публічно-правові відносини; прозора політика; административная сфера; предоставление административных услуг; государственное управление; публично-правовые отношения; прозрачная политика